2022
DOI: 10.1186/s40780-022-00255-w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the safety and efficiency of robotic dispensing systems

Abstract: Background Although automated dispensing robots have been implemented for medication dispensing in Japan, their effect is yet to be fully investigated. In this study, we evaluated the effect of automated dispensing robots and collaborative work with pharmacy support staff on medication dispensing. Methods A robotic dispensing system integrating the following three components was established: (1) automated dispensing robot (Drug Station®), which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Studies not featuring an ADC or where the automated solution was not a dispensing cabinet, such as a dispensing robot, were excluded. 21 , 22 , 23 , 24 , 25 , 26 , 27 If omitted or delayed doses were not a measured outcome, these articles were excluded. 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 Qualitative research was not included.…”
Section: Resultsmentioning
confidence: 99%
“…Studies not featuring an ADC or where the automated solution was not a dispensing cabinet, such as a dispensing robot, were excluded. 21 , 22 , 23 , 24 , 25 , 26 , 27 If omitted or delayed doses were not a measured outcome, these articles were excluded. 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 Qualitative research was not included.…”
Section: Resultsmentioning
confidence: 99%
“…The “robotic dispensing system” in the community pharmacies prepares prescribed medicines. It consists of three parts 26 :. An automated dispensing robot operated by pharmacy support staff, An automated dispensing robot for powdered medication, and A bar-coded medication dispensing support system with personal digital assistance.…”
Section: Resultsmentioning
confidence: 99%
“…The findings also highlighted the importance of using prior knowledge, such as gene networks and gene annotations, to improve future ADR assessments. Community pharmacy Takase T, 2022 26 Japan To assess the impact on medication dispensing of automated dispensing robots and collaborative work with pharmacy support staff. Prospective study Prescriptions filled with each dispensing device during the study periods The total incidence of prevented dispensing errors was significantly reduced after the robotic dispensing system was introduced (0.204% [324/158,548] to 0.044% [50/114,111], p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…influenced by several factors such as having a qualified technical team, an adequate number of employees, classification criteria, the type of medicines dispensation system, and management tools that assist in controlling stocks. Studies have reported an improvement in stock accuracy after implementing a system that uses barcodes 22 , as well as improvements in inventory management and dispensing with the use of robotic systems for medicines dispensing 5,[23][24][25] .…”
Section: Discussionmentioning
confidence: 99%